Synaptic Localization and Function of Sidekick Recognition Molecules Require MAGI Scaffolding Proteins - Yamagata, Masahito (Society for Neuroscience, 2010)
Four transmembrane adhesion molecules—Sidekick-1, Sidekick-2, Down's syndrome cell adhesion molecule (Dscam), and Dscam-like—are determinants of lamina-specific synapse formation in the vertebrate retina. Their C termini are predicted to bind postsynaptic density (PSD)-95/Discs Large/ZO-1 (PDZ) domains, which are present in many synaptic scaffolding proteins. We identify members of the membrane-associated guanylate kinase with inverted orientation (MAGI) and PSD-95 subfamilies of multi-PDZ domain proteins as binding partners for Sidekicks and Dscams. Specific MAGI and PSD-95 family members are present in distinct subsets of retinal synapses, as are Sidekicks and Dscams. Using Sidekick-2 as an exemplar, we show that its PDZ-binding C terminus is required for both its synaptic localization in photoreceptors and its ability to promote lamina-specific arborization of presynaptic and postsynaptic processes in the inner plexiform layer. In photoreceptor synapses that contain both MAGI-1 and PSD-95, Sidekick-2 preferentially associates with MAGI-1. Depletion of MAGI-1 from photoreceptors by RNA interference blocks synaptic localization of Sidekick-2 in photoreceptors without affecting localization of PSD-95. Likewise, depletion of MAGI-2 from retinal ganglion cells and interneurons interferes with Sidekick-2-dependent laminar targeting of processes. These results demonstrate that localization and function of Sidekick-2 require its incorporation into a MAGI-containing synaptic scaffold.